The association between metabolic syndrome and hypothyroidism in school-aged obese children - Alkilany, Zeina Fawaz; Chreitah, Ahmad; Zreik, Youssef (Journal of medical and pharmaceutical sciences, 2023)
Background: Subclinical hypothyroidism (SCH) is considered the most common hormonal disorder observed in obese children. SCH and metabolic syndrome (MS) are characterized by a set of common metabolic disorders such as visceral obesity, elevated TG (Triglycerides), T2DM (Type 2 diabetes mellitus), low HDL-C (High-density lipoprotein cholesterol), and therefore, undetected hypothyroidism may impair metabolic control and increase cardiovascular risk in patients with MS. Objectives: The purpose of this study is to find out the association between having MS and the occurrence of SCH in overweight and obese Syrian children aged 5 - 14 years.Methods: An observational cross - sectional analytic study was conducted on 90 overweight and obese patients aged 5-14 years (38 males 42.2% and 52 females 57.8%) who were followed up at the pediatric endocrine clinic at Tishreen University Hospital in Latakia from Aug’21 to July’22 and who met the eligibility criteria and had complete data.Results: SCH is increased in the presence of MS and with a higher incidence in females compared to males. Also, SCH increased in obese children more than overweight children.A positive correlation was observed between Thyroid-stimulating hormone (TSH) and TG levels, and a negative correlation was observed between TSH and HDL levels. Conclusion:  MS might increase the risk of SCH and the association between these two disorders may be bidirectional. Patients with MS and SCH should be monitored prospectively as an early intervention might play a role in reversing risk factors responsible for CVD (cardiovascular disease).
Keywords: metabolic syndrome; subclinical hypothyroidism; Children; Obesity; Syria